Management of Change Inspired by the NAIP - Devakumar, C.; Rao, D. Rama; Pandey, P. S.; Ezekiel, R.; Srivastava, A. P.; Ramasundaram, P.; Misra, R. P.; Kochhar, Sudhir (Indian Farming, 2015)
The ICAR has truly shown the way for other leading institutions and universities to systematically engage in developing toolkit of policies, internal guidelines and manuals of operating procedures for each of the management aspects for the promotion of innovations and change management.